Is the infectiousness of dogs naturally infected with Trypanosoma cruzi associated with poly-parasitism? - Enriquez, G F (2016)
Fil: Enriquez, G.F. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Laboratorio de Eco-epidemiología; Argentina.